At vælge det sunde fra: En diskursanalytisk undersøgelse af Sundhedsstyrelsens italesættelse af patienters - Møller, Jane Ege (Academic Quarter | Akademisk kvarter, 2015)
A recurring challenge in health promotion and prevention practice is the phenomenon of people choosing not to follow the health advice given by professionals, the people who appear to be ‘non-motivated’ for a healthy lifestyle. This phenomenon is the subject of this article. Based on the concepts of akrasia (weakness of the will) (with an inspiration from Martha C. Nussbaum and Alaisdair MacIntyre) and rationality of des-interest, (as proposed by Sam Paldanius) it unfolds a theoretical and philosophical framework for understanding the rationales that lie behind not following recommended health guidelines. Through an empirical analysis of the case of Poul, a diabetes2patient that refuses to change his lifestyle, the article shows how not choosing the healthy lifestyle must not be understood as only an irrational lack of motivation. The concepts akrasia and des-interest contribute to an understanding of how human reflections on the ’right choice’ is an ongoing and time-extended process, involving incommensurable goods, resistance and uncertainty as to finding the perfect balance between the conflicting desires that we as humans are subjected to